2011
DOI: 10.1016/j.jim.2011.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficiency of antibody selection from semi-synthetic scFv and non-immune Fab phage display libraries against protein targets for rapid development of diagnostic immunoassays

Abstract: Rapid development of diagnostic immunoassays against novel emerging or genetically modified pathogens in an emergency situation is dependent on the timely isolation of specific antibodies. Non-immune antibody phage display libraries are an efficient in vitro method for selecting monoclonal antibodies and hence ideal in these circumstances. Such libraries can be constructed from a variety of sources e.g. B cell cDNA or synthetically generated, and use a variety of antibody formats, typically scFv or Fab. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 25 publications
3
39
1
Order By: Relevance
“…One of the clones had higher affinity as Fab than as scFv-CL fragment, while the other two lost either some or all of their affinities. As suggested by Chan et al (2011), structural changes might occur at variable domains upon conversion of the scFv to Fab, which may lead to change or loss of specificity. Also, in the case of the anti-STR and anti-PSA antibodies, the scFvs were analyzed as fusions with alkaline phosphatase, which is known to form dimers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the clones had higher affinity as Fab than as scFv-CL fragment, while the other two lost either some or all of their affinities. As suggested by Chan et al (2011), structural changes might occur at variable domains upon conversion of the scFv to Fab, which may lead to change or loss of specificity. Also, in the case of the anti-STR and anti-PSA antibodies, the scFvs were analyzed as fusions with alkaline phosphatase, which is known to form dimers.…”
Section: Discussionmentioning
confidence: 99%
“…By using synthetic repertoires, the frameworks with the most favorable biophysical characteristics can be chosen as the library templates supporting the development of the retrieved antibodies into desirable final products (Tiller et al, 2013). However, scFv clones derived from synthetic libraries are sometimes unable to fold correctly or do not retain their affinity after conversion to a Fab or IgG format (Chan et al, 2011). Therefore, efficient and fast cloning methods are needed for the conversion of multiple clones from scFv to the more conventional formats to detect the best candidates for further development.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the presence of the constant heavy 1 and constant light domains may influence conformational characteristics of the V H and V L fragments. Compared with the scFv format, certain reports have described the increased capacity of selected Fabs to retain antigen specificity when converted to a full-length IgG antibody (34). In addition to favorable biochemical properties, in vivo studies demonstrated the biological potential of Fab antibody fragments.…”
Section: Fab-piii Displaymentioning
confidence: 99%
“…Briefl y, a MaxiSorp immunotube (Nunc) was coated with 200 g/ml of Mtb -derived mycolic acid dissolved in n-hexane, after which the hexane was allowed to evaporate overnight at 4°C. Screening of the library was performed on antigen coated immunotubes essentially as described previously for protein antigens and modifi ed for lipid antigens ( 19 ). Briefl y, Fab-phage were incubated with coated immunotubes for 2 h at room temperature followed by washing with PBS/0.5% Tween-20 to remove nonspecifi c bound phage; specifi cally bound phage were then eluted by digestion with trypsin solution for 30 min at 37°C.…”
Section: Phage Panning and Igg Expressionmentioning
confidence: 99%